The Relationship Between Quality of Life of Early Adulthood COVID-19 Survivors Who Have Received the COVID-19 Vaccine and Those Who Have Not Received the COVID-19 Vaccine and its Review In Islamic Perspective - Mashun, Ismah Fauziah; Susilowati, RW; Arsyad, M. (Fakultas Kedokteran Universitas YARSI, 2023)
Background: Coronavirus Disease 2019 (COVID-19) is caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). There was a decrease in the quality of life score during the COVID-19 pandemic. One of the efforts of the Indonesian government in dealing with the COVID-19 problem is by carrying out the COVID-19 vaccination. COVID-19 vaccination has halved deaths from COVID-19 globally. This study aims to determine the relationship between the quality of life of COVID-19 survivors in early adulthood who have received the COVID-19 vaccine and those who have not received the COVID-19 vaccine and the review according to the Islamic religion. Methods: This research is an analytic survey with a cross-sectional approach. The method of determining the sample in this study used non-random sampling with consecutive sampling techniques with a total sample of 60 respondents. Data collection was carried out using a questionnaire. Results: The results showed that the earliest adult COVID-19 survivors who had received the COVID-19 vaccine had a good quality of life 19 (80.0%). In contrast, the majority of early adult COVID-19 survivors who had not received the COVID-19 vaccine had a good quality of life, the mediocre 20 (87.0%). The relationship between the quality of life of COVID-19 survivors in early adulthood who have received the COVID-19 vaccine and those who have not received the COVID-19 vaccine has a value of p = 0.001 (p <0.05). Conclusion: There is a relationship between the quality of life of COVID-19 survivors in early adulthood who have received the COVID-19 vaccine and those who have not received the COVID-19 vaccine.